2013
DOI: 10.1016/j.ydbio.2012.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Gene regulation by the lysine demethylase KDM4A in Drosophila

Abstract: Lysine methylation of histones is associated with both transcriptionally active chromatin and with silent chromatin, depending on what residue is modified. Histone methyltransferases and demethylases ensure that histone methylations are dynamic and can vary depending on cell cycle- or developmental stage. KDM4A demethylates H3K36me3, a modification enriched in the 3' end of active genes. The genomic targets and the role of KDM4 proteins in development remain largely unknown. We therefore generated KDM4A mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 45 publications
2
36
1
Order By: Relevance
“…Functions independent of catalytic activity also could be expected; in line with this, JMJD2C and other JMJD2 family members were reported to interact with the SWI/SNF complex (52). Interestingly, a recent study demonstrated that while some transcriptional changes elicited by loss of the Drosophila JMJD2 family member, dKDM4A, involved its catalytic activity, most target genes did not appear to be regulated by histone demethylation (61).…”
Section: Discussionmentioning
confidence: 78%
“…Functions independent of catalytic activity also could be expected; in line with this, JMJD2C and other JMJD2 family members were reported to interact with the SWI/SNF complex (52). Interestingly, a recent study demonstrated that while some transcriptional changes elicited by loss of the Drosophila JMJD2 family member, dKDM4A, involved its catalytic activity, most target genes did not appear to be regulated by histone demethylation (61).…”
Section: Discussionmentioning
confidence: 78%
“…These findings suggest that some of these genes are indirect dKDM4A targets and that epigenetic regulation can be either dependent on or independent of the demethylase catalytic activity (44).…”
Section: Kdm4a Functionsmentioning
confidence: 92%
“…Genes repressed or activated by Drosophila melanogaster KDM4A (dKDM4A) were reported to not require KDM4A catalytic activity for expression; nevertheless, activated genes require its demethylase activity for proper expression (44). These findings suggest that some of these genes are indirect dKDM4A targets and that epigenetic regulation can be either dependent on or independent of the demethylase catalytic activity (44).…”
Section: Kdm4a Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histone methyltransferase Set2 in yeast and nuclear receptor SET domain-containing 1 (NSD1) in humans control the methylation of H3K36 forming mono-, di- or tri-methylation on K36 (abbreviated as H3K36me1, H3K36me2 or H3K36me3, respectively) (Wagner and Carpenter, 2012). Conversely, the histone demethylases such as KDM2, KDM4 and KDM8 have been shown to specifically demethylate H3K36me (Crona et al, 2013; Hsia et al, 2010; Jones et al, 2010; Lin et al, 2012; Tsukada et al, 2006). There are two KDM2 paralogs in vertebrates: KDM2A (also known as FBXL11, JHDM1A, and Ndy2) and KDM2B (also known as FBXL10, JHDM1B, and Ndy1) (Allis et al, 2007; Cloos et al, 2008; Tsukada et al, 2006).…”
Section: Introductionmentioning
confidence: 99%